2021
DOI: 10.24832/kpt.v30i2.781
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Archaeology Study on the Drilling Techniques of Neolithic Stone Bracelet from Purbalingga

Abstract: Abstract. The stone bracelet is a neolithic artifact crafted by drilling techniques. Traces of stone bracelet workshop activities in Central Java were found in Purbalingga, which is spread across the North Serayu Mountains between Kali Tungtunggunung and Kali Laban. This study is based on the previous research hypothesis, which states that the manufacture of stone bracelets is carried out by drilling techniques using bamboo wulung (Gigantochloa atroviolacea). This study aims to prove this hypothesis. An experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…In contrast to the MSEA, perforated disks are hardly ever found in Insular Southeast Asia (ISEA). Perforated disks are occasionally associated with the production of semiprecious stone bracelets from the Javanese Late-Neolithic sites (Heekeren, 1972;Soejono et al, 1993;Sulistyarto et al, 2021) that are morphologically different to those found in MSEA sites. Perforated disks from the Javanese Neolithic sites are generally polished with a large hole in the center that appears to fit on the wrist.…”
Section: Limitation and Regional Context Of Perforated Disks And Groo...mentioning
confidence: 99%
“…In contrast to the MSEA, perforated disks are hardly ever found in Insular Southeast Asia (ISEA). Perforated disks are occasionally associated with the production of semiprecious stone bracelets from the Javanese Late-Neolithic sites (Heekeren, 1972;Soejono et al, 1993;Sulistyarto et al, 2021) that are morphologically different to those found in MSEA sites. Perforated disks from the Javanese Neolithic sites are generally polished with a large hole in the center that appears to fit on the wrist.…”
Section: Limitation and Regional Context Of Perforated Disks And Groo...mentioning
confidence: 99%